Soil micromorphology of the sedimentary samples from Anta 1 de Vale da Lage, Tomar, Portugal - Adewumi, Opeyemi Lateef (2019)
This master thesis is based on the soil micromorphological study of the sedimentary samples from Anta 1 de Vale da Laje site, located in Tomar, Portugal. The site of Anta 1 de Vale da Laje is one of the sites currently under study within the research framework of the projects Landscape occupation strategies during the Holocene in the Middle Tagus (Es.Ter.Tejo) and Moving tasks across shapes: the agro-pastoralists spread from and into the Alto Ribatejo (MTAS). Asides the stratigraphic problems of the site, it remained unclear the modification successions in time, of the monument and the processes that can be attributed to their sequencing, which were scopes of the abovementioned projects. Micromorphological study of human impact and natural processes on the environment has been reliant on the interpretation from the study of the undisturbed palaeosols. This study applied the methodological approach of soil micromorphological analyses to understand both the stratigraphic sequence and the evolution of the megalithic tomb of Anta 1 de Vale da Laje site where stratigraphic continuity and discontinuity were observed. The result of the analyses recognized six (6) periods of activities and three (3) phases of site evolution, as well as identification of human activities relating to agricultural practices, constructions and natural processes such as weathering, leaching, and erosion resulting from impact of rainfall.